(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In the modern era, information power is the most potent form of power. Having access to the latest information gives one the ability to manipulate and influence. Those in the media and manufacturing the discourse use it as an effective tool for shaping public opinion. Investigative journalists conduct thorough investigations into political issues or cases of corruption. Usually, their investigation involves long-term research through which they come across astonishing realities. This long-term involvement with single issues of public interest equips the journalists with informational power. That is precisely why investigative journalists wield such power and influence. Their language serves as a potent tool, enabling them to shape, reshape, and ultimately change public opinion. In a way, they perform political eugenics as talk shows on current political issues help them in purifying or sterilizing public opinion. This determines their performativity. The status quo is maintained by conducting programs on regular basis. John Austin described each speech act to take place as a continuation of three steps namely illocutionary, locutionary and perlocutionary. He also initiated the idea of performativity. Performativity is related to the locutionary act. Perlocutionary act can be intended or unintended but when intentional, it causes a state of mind named as perlocutionary effect (Nordquist, 2018) in the hearer, which eventually makes him/her act in the desired way. In this article, this desired perlocutionary effect could be observed in the voting outcomes in Elections 2018 in Pakistan.